The Efficacy of Intraoperative Ketamine-Haloperidol for Prevention of Catheter-related Bladder Discomfort After Lumbar Spinal Stenosis Surgery - Khajavi, Mohammad Reza (Oman Med J, 2019)
OBJECTIVES: Catheterization of urinary bladder during surgery frequently leads to agitation of the patient in the recovery room, especially in those patients who remain catheterized after gaining consciousness. We hypothesized that administration of a combination of ketamine-haloperidol (KH) before urinary catheterization would reduce the incidence of catheter-related bladder discomfort (CRBD) while reducing some adverse effects of ketamine in the postoperative period. METHODS: A total of 119 male patients who underwent lumbar spinal stenosis surgery were randomized into three groups. The KH group consisted of 39 patients who received KH just before urinary catheterization. The second arm of the study including 40 patients who received pethidine-haloperidol (PH). The control (C) group consisted of 40 patients who received normal saline as a placebo. We sought to determine the incidence and severity of CRBD at arrival in recovery and one, six, and 24 hours after. RESULTS: The incidence of CRBD upon arrival in the recovery room was 17.9% in the KH group, and 52.5% and 55% in the PH and C groups, respectively. The incidence of CRBD was signiﬁcantly lower in the KH group at arrival in the recovery room. The severity of CRBD was lower in the KH group at one and six hours of surgery (p < 0.007). There was no significant difference 24 hours after surgery. CONCLUSIONS: Intravenous administration of KH before urinary catheterization effectively decreases the incidence and severity of postoperative CRBD while reducing adverse effects attributed to ketamine.